Palynological studies of Maastrichtian to paleocene sediments exposed at Okpekpe, western flank of Anambra Basin, Edo State, Nigeria - N.S. Igbinigie; A.H. Akenzua-Adamczyk (Journal of Applied Sciences and Environmental Management)
Outcrop samples were collected at a road cut along Okpekpe road in the western part of the Anambra Basin with a view to establishing the age of the sediments and their depositional environment. These consist mainly of shales, sandstone, siltstone and heterolith. The samples were processed and analyzed using standard palynological procedures. Index fossils of stratigraphic significance were used for dating of the sediments. An extremely poor recovery of palynomorphs characterized by Acrostichum aureum, Laevigatosporites sp, Verrucatosporites sp, Cingulatisporite sornatus, Deltodosporasp, Lycopodium spp, Cyathidites minor, Echitricolporites triangulatus, Retitricolporites irregularis, Retitricolporites sp, Liliacidites sp, Longapertites marginatus, Longapertites sp, Erecipites sp., Monosulcites perspinosus, Retistephanocolpites williamsi, Echiperiporites estalae, Dodoneaviscosa, Echitriporite strianguliformis, Periretipollis spinosus, Marginipollis concinnus, Cupaniedites sp., Gleicheniidites senonicus Andalusiella polymorpha and Andalusiella sp was noticed. A Maastrichtian-Paleocene age and a continental depositional environment were assigned to the sediments.